GDF-15 is a potential candidate biomarker for an elevated risk of cardiotoxicity in breast cancer patients receiving neoadjuvant dual anti-HER2 therapy - Tian, Chunyu; Zhang, Hongxu; Liu, Jianping; Xu, Mengze; Ma, Lihui (Frontiers in Pharmacology, 2024)
Objective Growth differentiation factor 15 (GDF-15) is a stress-responsive cytokine that regulates myocardial injury, cardiac overloading pressure, and inflammation and is related to the risk of cardiovascular diseases and events. The current study aimed to investigate the correlation of GDF-15 levels with clinical features, biochemical indices, and especially the risk of cardiotoxicity in breast cancer patients receiving neoadjuvant dual anti-HER2 therapy. Methods A total of 103 HER2-positive breast cancer patients who underwent neoadjuvant dual anti-HER2 therapy (trastuzumab and pertuzumab plus chemotherapy) were included. Serum GDF-15 levels before neoadjuvant treatment were detected by enzyme-linked immunosorbent assay. Cardiotoxicity was evaluated during neoadjuvant therapy by referring to a decline of ≥10 percentage points in the left ventricular ejection fraction from baseline to an absolute level less than 50%. Results GDF-15 exhibited a skewed distribution, with a median level of 714 (range: 207–1805) pg/mL. GDF-15 was positively correlated with age (p = 0.037), diabetes (p = 0.036), and the N-terminal pro-brain natriuretic peptide level (p = 0.013) and positively correlated with the total cholesterol level (p = 0.086) and troponin T level (p = 0.082), but these correlations were not statistically significant. A total of 6.8% of patients experienced cardiotoxicity during neoadjuvant therapy. By comparison, the GDF-15 level was greater in patients who experienced cardiotoxicity than in those who did not (p = 0.008). A subsequent receiver operating characteristic curve revealed that GDF-15 predicted cardiotoxicity risk, with an area under the curve of 0.803 (95% CI: 0.664–0.939). After multivariate adjustment, GDF-15 independently predicted a greater risk of cardiotoxicity (p = 0.020). Conclusion GDF-15 is a candidate biomarker for increased risk of cardiotoxicity in breast cancer patients receiving neoadjuvant dual anti-HER2 therapy.